Penyusunan Laporan Keuangan Berdasarkan SAK EMKM pada UMKM (Studi Kasus Salon Noni di Kuala Pembuang) - Pahlevi, Olvi Salavia; Mulyanto, Sigit (Keizai, 2020)
The preparation of financial reports is needed by MSME owners to support their business because with financial reports they can find out the number of profits and losses they get. The purpose of this research is to compile the Noni Salon MSME Financial Statements based on SAK EMKM. This type of research is descriptive through a qualitative approach. The results showed that Salon Noni did not record and prepare financial reports based on SAK EMKM because they did not understand how to prepare the financial statements. Salon Noni MSME Financial Statements as of December 31, 2019, with total assets owned by MSMEs of IDR 140,534,000, total liabilities and equity of IDR 140,534,000, Salon Noni MSME Profit and Loss Report shows net income of IDR 75,217,000. Notes on Salon Noni MSME Financial Statements have been prepared in accordance with SAK EMKM.